FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIV PADA WPS (WANITA PEKERJA SEKS) DI KLINIK VCT (VOLUNTARY COUNSELING AND TESTING) WILAYAH KERJA PUSKESMAS PADANG BULAN KOTA MEDAN - Pasaribu, Riska Susanti; ., Asfriyati; Andayani, Lita Sri (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Exposure to HIV patients in North Sumatra until March 2016 the cumulative number of HIV cases was 11,295 people. HIV spread is more vulnerable to women, HIV can be transmitted through sex, this can be caused by employment status such as female sex workers (WPS). The purpose of this study was to determine the factors associated with HIV incidence in WPS. The study used a descriptive analitic research design with a cross sectional approach. The location of the study in the VCT clinic in the Padang Bulan Medan Health Center working area. The population of this study were all WPS who conducted examinations at the Padang Bulan Health Center. The sample of this study amounted to 140 people. Data analysis by Chi Square and multiple logistic regression. The results showed that there was a relationship between age (p = 0.004), education (p = 0.035), marital status (p = 0.001), age at first time having sex (p = 0.001), consistency in condom use (p = 0.0001) and knowledge (p = 0,0001) with HIV incidence in WPS. The conclusion was that there was the between age, education, marital status, age at first having sex, consistency of condom use, knowledge of HIV incidence in WPS. It is recommended that health workers at the Padang Bulan health center should approach WPS routinely to be localized to conduct HIV examinations in VCT clinics and provide information on prevention of HIV transmission by using condoms.